Alimentary and nutritional aspects of users of the popular restaurant "Mesa do Povo" - Araújo, Fábio Ângelo Lima Verde de; Almeida, Maria Irismar; Bastos, Valéria Carneiro (Saúde e Sociedade, 2007)
The aim of this study was to examine alimentary, nutritional and socio-economic aspects of the users of Mesa do Povo, a popular restaurant in the city of Fortaleza, state of Ceará. Fifty-one customers were randomly selected in order to answer questionnaires using the 24-hour recall method concerning eating habits. The sample was stratified into sex and adaptation levels. Food consumption was evaluated according to the Diet Quality Index (DQI) and caloric adequacy was assessed through the Adapted Eating Pyramid. Macro and micronutrients presented adequacy based on Dietary Reference Intakes (DRI). After frequenting the restaurant, 42.85% of the men and 37.5% of the women answered that they are consuming more green vegetables. Among health problems, hypertension linked to diabetes mellitus (11.76%) and diabetes mellitus associated with cardiovascular disease (3.92%) were the most cited. Regarding total calories, the average intake was 2,278.95 calories for men and 1,785.65 calories for women, and there was a significant difference between sexes. Calorie inadequacy was evident in 31.4% below the recommended standard and 49% above that. It was ascertained that 100% of the users present protein caloric contribution within the recommended standard, namely, 94.12% for carbohydrates and 90.2% for fat adequate to what is recommended. Data revealed that calcium and tocopherol presented the lowest adequacy in the users' diet; however, there was a satisfactory adaptation concerning the average content in vitamins and minerals. Adjustments are necessary to improve the management of services by means of selective and adequate criteria in order to reach a larger number of vulnerable users in nutritional and socio-economic aspects.